The Development of Strategic Resilience in Airline Industry During Covid-19 : Case Finnair - Ackrén, Aino Emilia (My University, 2024)
The interest in the strategic resilience of companies have grown in research over the past years. Previous research on resilience has strongly focused on the long-term strategies of companies, and resilience has been seen as a response to quick and unexpected disruptions. However, not much research on resilience has been done as a way of anticipating and preparing for future disruptions. Studying resilience is necessary because of its positive effects on companies' business operations. In addition, it has been found in previous studies that resilience is considered challenging to define and many different methods of determination make it difficult to understand resilience. The global pandemic Covid-19 made the operations of many companies difficult and drove them to a completely new and unexpected situation, which forced them to amend the strategy and expand operations to survive the pandemic. Many companies found that they cannot react quickly enough to sudden changes coming from the outside, and they do not have enough skills and understanding of resilience, flexibility, or agility, which caused many bankruptcies in many different industries. Airlines in particular experienced great difficulties when the global travel restrictions came into force and at the same time drove the airlines' operations down. This study focuses on the development of strategic resilience in a Finnish airline. Qualitative research was conducted by collecting data in the form of interviews from the Case company, Finnair Oyj. Employees in management positions with several years of work experience in the company were selected to be interviewed. The results of the study show that in the airline industry, focusing on strategic resilience is necessary to guarantee the continuity of operations. The findings emphasize wider and more frequent creation of scenarios, development of a structured operating model, closer cooperation with stakeholders and other companies operating in the field, more precise monitoring of the cost structure, and the effects of personnel commitment in the implementation of major changes. The pandemic itself was felt to have strengthened the importance and understanding of resilience, which will influence future strategy planning.
Keywords: fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development